Biochemical Fingerprints of Some Endemic Plants Growing in Gypsum Soils: Attenuated Total Reflection-Fourier Transform Infrared (ATR-FTIR) Spectroscopic Study - Ayşenur Kayabaş; Ertan Yıldırım (European Journal of Biology)
Objective: The aim of this study is to reveal the biochemical fingerprints of Achillea gypsicola Hub.-Mor., Alyssum nezaketiae Aytaç & H.Duman, Onobrychis germanicopolitana Hub.-Mor. & Simon, Paracaryum paphlagonicum (Bornm.) R.Mill and Thymus leucostomus Hausskn. et Velen. grown in extreme gypsum habitats with the Attenuated total reflection-Fourier transform infrared (ATR-FTIR) technique, and to determine the differences and densities of organic and inorganic compounds reflected by extreme environmental conditions. Materials and Methods: Using ATR-FTIR spectra, the chemical content of endemic plants was elucidated. In addition, band intensities were calculated using the ATR-FTIR spectra. By doing soil analysis, the physical and chemical properties of the regions where the plants grow were tried to be understood. Results: As a result of the detailed analysis of the ATR-FTIR spectra, it was understood that the chemical substance content was similar, but the amount was different from plant to plant, regardless of soil. These results showed that the same plant species contain different amounts of chemicals. Conclusion: FTIR spectroscopy is an effective tool that reveals the biochemical fingerprints of plants by contributing to the determination of organic and inorganic compounds in the structures of plants grown on gypsum substrates. Our results provided evidence for the presence of sulfate from organic molecules and the presence of gypsum and calcium oxalate from inorganic compounds. This study, which is the first to determine the biochemical fingerprints of plants growing in gypsum habitats in Turkey, will enrich the generality of future studies and the interpretation of other gypsophytes in the world.